2008
DOI: 10.1080/02699050801938983
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in complex visual information processing after mild TBI: Electrophysiological markers and vocational outcome prognosis

Abstract: The findings suggest that individuals with symptomatic mTBI can present selective deficits in complex visual information processing that could interfere with vocational outcome. ERP paradigms such as those employed in this study thus show potential for evaluating outcome prognosis and merit further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 67 publications
(92 reference statements)
1
33
0
Order By: Relevance
“…[4][5][6][7][8] For example, a long-term analysis of visual event-related potentials (VERPs) in 17 patients with TBI reported deficits in complex visual integrative tests. 9 Further, reduced amplitude and delayed latency of VERPs have been observed in patients with moderate TBI. 10 Often, blast injury is comorbid with other types of injury such as blunt injury.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] For example, a long-term analysis of visual event-related potentials (VERPs) in 17 patients with TBI reported deficits in complex visual integrative tests. 9 Further, reduced amplitude and delayed latency of VERPs have been observed in patients with moderate TBI. 10 Often, blast injury is comorbid with other types of injury such as blunt injury.…”
Section: Discussionmentioning
confidence: 99%
“…9,19,23,25,26,31,46 Moreover, abnormal ERP components were found even when concussed athletes did not report symptoms. 23,32,45,46 Taken together, ERP studies have shown that MTBI and sports concussion produce mild but persistent cerebral changes that can be observed even when patients are asymptomatic.…”
Section: Event-related Potentials Mtbi and Concussionmentioning
confidence: 99%
“…In particular, Gosselin and associates (2006) reported amplitude reductions of N1, P2, and P3 components following concussions. In other studies, the effects of concussion (or mild brain trauma) were detected only for the late ERP components (P3), mostly affecting amplitude (De Beaumont et al, 2007), but also affecting latency (De Beaumont et al, 2009;Lachapelle et al, 2008). In fact, the effects of concussion on P3 were long-lasting, and could be detected 30 years after the inciting event (De Beaumont et al, 2009).…”
Section: Russo Et Almentioning
confidence: 99%